Brachyxenia subtruncata sp. nov. (Orthoptera: Acrididae: Calliptaminae), a new short-horned grasshopper species from India - Gupta, Sunil Kumar; Chandra, Kailash; Dang, Yan (Zootaxa, 2018)
Brachyxenia subtruncata sp. nov. is described from Durg district, Chhattisgarh, India. The description is based on morphological characters of male.